Nuclear miR-122 directly regulates the biogenesis of cell survival oncomiR miR-21 at the posttranscriptional level. Issue 4 (14th December 2017) - Wang, Dong; Sun, Xinlei; Wei, Yao; Liang, Hongwei; Yuan, Min; Jin, Fangfang; Chen, Xi; Liu, Yuan; Zhang, Chen-Yu; Li, Limin; Zen, Ke
Abstract: Hepatic miR-122 can serve as a pro-apoptotic factor to suppress tumorigenesis. The underlying mechanism, however, remains incompletely understood. Here we present the first evidence that miR-122 promotes hepatocellular carcinoma cell apoptosis through directly silencing the biogenesis of cell survival oncomiR miR-21 at posttranscriptional level. We find that miR-122 is strongly expressed in primary liver cell nucleus but its nuclear localization is markedly decreased in transformed cells particularly in chemoresistant tumor cells. MiRNA profiling and RT-qPCR confirm an inverse correlation between miR-122 and miR-21 in hepatocellular carcinoma tissues/cells, and increasing or decreasing nuclear level of miR-122 respectively reduces or increases miR-21 expression. Mechanistically, nuclear miR-122 suppresses miR-21 maturation via binding to a 19-nt UG-containing recognition element in the basal region of pri-miR-21 and preventing the Drosha-DGCR8 microprocessor's conversion of pri-miR-21 into pre-miR-21. Furthermore, both in vitro and in vivo studies demonstrate that nuclear miR-122 participates in the regulation of HCC cell apoptosis through modulating the miR-21-targeted programmed cell death 4 (PDCD4) signal pathway.